Literatura(s), Livros(s) e cinemas(s): uma leitura intermidiática de Histoires(s) du Cinéma, de Jean-Luc Godard - Tamiris Lalesca da Rocha (2020)
This dissertation aims at analysing the series Histoire(s) du cinéma (1988-1998), written by Jean-Luc Godard, and its relation with his book of the same title, which was published by Gallimard, in 1998. Besides considering certain issues on its transition from the cinema to the book, this paper also presents a study on how the book and the literature are shown in the series. The interest in literature, edition, cinema and intermedial studies, motivated the choice of such multiple masterpiece which starts from literature to establish in the cinema and then, become a book. The importance of this research is then, based on the relevance of the intrinsic dialogue between the different fields of its artistic, literary, editorial and theorical production, which focus, mainly, on the work of one of the most important cinema’s name, with all the ramifications which revolutionized the way of thinking and making cinema. Therefore, it originally contributes to the intermediality, considering that great part of the studies which relate literature and cinema consider these dialogues but, under the perspective of making the book into a film, and not the film into a book. Moreover, it explores the book´s representation in the cinema, discussing ideas about materiality in the context of Literary and Editorial Studies.